2018 Argentina: haunted by instability once again - Margheritis, Ana (Revista de Ciencia Política, 2019)
2018 was a rocky year for Argentina. Economic instability put it on the brink of crisis again and eroded the government’s credibility. This article provides an analysis of the main social, political and economic events affecting Argentina’s domestic politics and foreign policy. It accounts for selected issues, with an emphasis on changes in public policies and implications for the upcoming years. The argumentative thread focuses on the consequences of Argentina’s being haunted by the spectre of another debacle. Within changes in public policies, the focus is on the end of a gradual approach to structural changes and initiatives related to population and human mobility across borders—a policy area that has required increasing attention and resources of late